IMPLEMENTASI PERAN MENUMBUHKAN KEBIASAAN MENABUNG SEJAK DINI BERBASIS PERBANKAN SYARIAH DI TADIKA TINTA KHALIFAH MALAYSIA - Alya Saskia; Alfi Amalia (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to analyze the implementation of education in fostering savings habits from an early age through the introduction of basic concepts of Islamic banking to children at Tadika Tinta Khalifah Al Fikh Orchard, Malaysia. Financial literacy is a crucial aspect that needs to be introduced from an early age so that children can understand the value of money and develop responsible financial behaviors. However, in reality, many children still lack a consistent understanding of and habit of saving. This study employs a descriptive qualitative approach to describe the learning process and the role of teachers in fostering saving habits among young children. Data were collected through direct education, semi-structured interviews with teachers, documentation of activities, and a literature review. The results indicate that implementing savings programs aligned with Islamic banking values—such as trustworthiness, discipline, and frugality—can help foster saving habits in children. Additionally, the roles of teachers and the learning environment are crucial in providing financial explanations that are easy for children to understand and engaging for them. This study concludes that integrating Islamic financial values into early childhood education can support the development of saving habits and financial awareness from an early age